CGIAR Research Program on Maize - Plan of Work and Budget 2019 - CGIAR Research Program on Maize (CGIAR Research Program on Maize, 2019)
The CGIAR AgriFood System Research Program MAIZE is an international collaboration between more than 300 partners from the public and private sectors, national institutions, international research organizations and seed companies. This unique partnership seeks to mobilize global resources in maize research and development to achieve a greater strategic impact on maize-based farming systems in Africa, South Asia and Latin America.